A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 5 years ago
Can someone show the steps to solve this other equation?
2(3t+1)5=t(t+2)
anonymous
 5 years ago
Can someone show the steps to solve this other equation? 2(3t+1)5=t(t+2)

This Question is Closed

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0just multiply then solve for t 2(3t+1) will give 6t+2 , and t(t+2) will give tt2 = 2 equalize them 6t+2=2 6t=4 t=4/6

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0I understood the 2(3t+1) part but i dont get the rest.

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0try to read again, t(t+2) will give tt2 = 2 now substitute them in the original formula 6t+2 (from 2(3t+1)) = 2 (from t(t+2)) 6t+2=2 6t=4 t=4/6

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.06t+25=tt2 6t3=2 6t=32 6t=1 t=1/6

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0man I forgot the minus 5 ><.. 6t+25=2 6t3=2 6t=2+3 6t=1 t=1/6

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.06t+2=8t then 5 makes it 3t? How'd you get 2?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0i got 2 by distributing the negative there to (t+2) which gave me t2
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.